A review of bovine spongiform encephalopathy and its management in Canada and the USA. (21st September 2010) - Lewis, Roxanne E.; Krewski, Daniel; Tyshenko, Michael G.
Geographic proximity and a long history of integration between US and Canadian cattle industries have resulted in similar management of BSE risk factors. Both countries have had a single imported case of BSE followed by multiple endemic cases of the bovine disease. Comparable risk management strategies have been put in place, such as a ban on the feeding of ruminant materials to other ruminants, a ban on the use of specified risk materials in human and animal feed, and targeted import policies designed to limit the possibility of introduction and propagation of BSE to and within the domestic cattle herd. Despite these similarities, Canada has had experienced a much greater economic challenge than the US in response to BSE due to its higher reliance on beef and cattle exports and the greater number of BSE cases detected within the country.